Little girl participating in the 1986 y-Walk - Brock, Trish (photographer):::Creator::::::::::::
Negative shows a close up of a little girl leaning up against a telephone pole at the corner of First Street and Santa Clara Street in downtown San Jose. She is a participant in the 1986 y-Walk and is carrying a balloon. Her tee shirt reads: "Walk for women. YWCA 1986." There are other men and women participants just beginning to cross the street to where the little girl is standing. The street sign above them reads: "N First St".